A Contemporary Approach of Las Meninas - Andreea-Irina Stoleriu (Anastasis: Research in Medieval Culture and Art)
The present study is meant to underline the importance of a famous work from the baroque period, Las Meninas, made by the painter Diego de Silva y Velásquez who has become a source of inspiration for future generations of artists. Numerous modern and contemporary artists have integrally or partially ”paraphrased” Velásquez’s composition by intercepting the portrait of revolutionary group for the time when it was created, extremely innovative regarding its compositional qualities and its hidden meanings which underlined the role and status of the artist in the context of a conservative society. Thus, the painting becomes the living proof of the way in which the artist manages to overcome the limitations of the social status of ordinary human beings, by portraying himself as a close friend of the royal family and by opening, through this type of representation, an important chapter in the history of portraiture.